(untitled) - Colander, David C. (Boston, 2006)
Written in an informal colloquial style, this student-friendly principles of economics textbook does not sacrifice intellectual depth in its quest for accessibility. The author's primary concern is to instill "economic sensibility" in the student. Colander emphasizes the intellectual and historical context to which the economic models are applied.
Keywords: Economics,Kinh tế